New taxa of oribatid mites from Korup National Park (Cameroon). The genus Pergalumna (Acari, Oribatida, Galumnidae), with description of three new species and a key to known species from the Ethiopian region - Ermilov, Sergey G.; Starý, Josef (Zootaxa, 2018)
Three new species of oribatid mites of the genus Pergalumna (Oribatida, Galumnidae) are described from litter and soil in the Korup National Park (Cameroon). Pergalumna jenoi sp. nov. differs from P. margaritata Mahunka, 1989 and P. pseudomargaritata Mahunka, 1994 by the presence of simple dorsosejugal suture, dentate anterior margin of the ventral plate, distinct reticulate pattern on the pteromorphs and dense stria on the genital plates, the localization of setal alveoli la posterior to porose areas Aa, and the absence of a median pore. Pergalumna tuberclesejugalis sp. nov. differs from P. margaritata and P. pseudomargaritata by the larger body size, the localization of porose areas Aa closer to lm than la, and setal alveoli h3 close and lateral to A2, the presence of sejugal porose areas, and the absence of a median pore and stria on the genital plates. Pergalumna grebennikovi sp. nov. differs from P. bifissurata Hammer, 1972 by the larger body size, the presence of smooth bothridial setae, well-developed interlamellar setae, reticulate anterior margin of pteromorphs, comparatively long prodorsal median ridge and a median pore, and the localization of setal alveoli la and porose areas Aa. An identification key to the known species of the genus Pergalumna from the Ethiopian region is presented.